2013
DOI: 10.4100/jhse.2013.84.15
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adaptogen supplementation on sport performance. A recent review of published studies

Abstract: Molinos, A. (2013). Effects of adaptogen supplementation on sport performance. A recent review of published studies. J. Hum. Sport Exerc., 8(4), pp.1054-1066. Objective: Adaptogens are a new class of metabolic regulators (plants from natural origin) which have been shown to increase the ability of organism to adapt environmental factors and to avoid body damage. These properties offer the possibility to utilize them to increase the performance in situations of mental and physical stress, and thus used it to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Recent research has found adaptogens to be promising in this application domain [ 13 – 15 ]. However, the results in this literature are mixed and therefore more research is needed so that we have a better understanding of adaptogens as ergogenic aids [ 14 ]. This present study attempts to make a small step towards such an understanding.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has found adaptogens to be promising in this application domain [ 13 – 15 ]. However, the results in this literature are mixed and therefore more research is needed so that we have a better understanding of adaptogens as ergogenic aids [ 14 ]. This present study attempts to make a small step towards such an understanding.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review on adaptogen supplementation and their capacity to enhance athletic performance was performed by Melinos A. [207], who highlighted the differences between adaptogens and other metabolic regulators, such as stimulants. Various adaptogen plants were discussed in this study; for example, Rhodiola rosea, Eleutherococcus senticosus, Schizandra chinensis and Panax ginseng showed encouraging results in improving physical performance, which can be applied to combat players.…”
Section: Natural Supplements: Importance and Advantages Over Syntheti...mentioning
confidence: 99%
“…Current and potential uses of these medicinal plants are associated with mental diseases and behavioural disorders, cognitive function and stress-induced diseases (anxiety, cardiovascular diseases, diabetes) [4,9,[15][16][17][18][19][20]. The intake of plant adaptogens is not associated with serious side effects [20,21].…”
Section: Introductionmentioning
confidence: 99%